Answer:
Step 1 : (5x-4)/2 = 2x-1 {Given}
__________________________________________________________
Step 2 : ((5x-4)/2) × 2 = 2 × (2x-1) {Multiplicative Property}
__________________________________________________________
Step 3 : (5x-4) = 4x-2 {Distributive Property}
__________________________________________________________
Step 4 : 5x - 4 + 4 = 4x - 2 + 4 {Addition property}
5x = 4x + 2
__________________________________________________________
Step 5 : 5x - 4x = 4x + 2 - 4x {Subtraction property}
x = 2